Exploring students' procedural flexibility in three countries - Jon R. Star; Dimitri Tuomela; Nuria Joglar-Prieto; Peter Hästö; Riikka Palkki; Miguel Á. Abánades; Johanna Pejlare; R. H. Jiang; Lijia Li; Ru-De Liu (SpringerOpen, 2022)
Abstract Background In this cross-national study, Spanish, Finnish, and Swedish middle and high school students' procedural flexibility was examined, with the specific intent of determining whether and how students' equation-solving accuracy and flexibility varied by country, age, and/or academic track. The 791 student participants were asked to solve twelve linear equations, provide multiple strategies for each equation, and select the best strategy from among their own strategies. Results Our results indicate that knowledge and use of the standard algorithm for solving linear equations is quite widespread across students in all three countries, but that there exists substantial within-country variation as well as between-country variation in students' reliance on standard vs. situationally appropriate strategies. In addition, we found correlations between equation-solving accuracy and students' flexibility in all three countries but to different degrees. Conclusions Although it is increasingly recognized as an important construct of interest, there are many aspects of mathematical flexibility that are not well-understood. Particularly lacking in the literature on flexibility are studies that explore similarities and differences in students' repertoire of strategies for solving algebra problems across countries with different educational systems and curricula. This study yielded important insights about flexibility and can push the field to explore the extent that within- and between-country differences in flexibility can be linked to differences in countries' educational systems, teaching practices, and/or cultural norms around mathematics teaching and learning.